The Legal Protection for Bank Customers in Automated Teller Machine (ATM) Transactions - Gultom, Qinnara Zegia (Program Studi Perbankan Syariah Universitas Pahlawan Tuanku Tambusai, 2025)
Objectives - This study aims to examine the legal safeguards for customers using the Automated Teller Machines (ATMs) of Bank BNI Biak Branch and to analyze the bank’s liability for any damages incurred during ATM transactions. The research focuses on identifying the extent of legal protection provided to customers and the mechanisms available for redress in case of transactional losses or fraud. Methods - This research employs a qualitative descriptive approach using both empirical and normative legal analysis. Data were obtained through interviews, document analysis, and literature studies to capture real cases and assess them within the framework of existing consumer protection laws. Results - The findings reveal that the provisions of Consumer Protection Law Number 8 of 1999 are consistent with the legal protections afforded to banking clients. Bank BNI Biak Branch provides compensation for losses resulting from operational errors or unlawful acts affecting ATM transactions. The study also emphasizes that banks are obliged to reimburse customer losses and implement restorative justice through banking mediation institutions, clear customer complaint procedures, increased product information transparency, and improved consumer education to minimize legal disputes. Civil disputes may also be resolved through established civil law procedures in court. Originality (Novelty) - This study contributes to the understanding of how consumer protection principles are applied specifically within the context of ATM transactions in regional banking institutions. It highlights the integration of restorative justice and mediation as preventive and corrective measures in resolving banking disputes. Implications - The results underscore the importance of strengthening institutional mechanisms for consumer protection in banking services. Policymakers and financial institutions can utilize these insights to enhance transparency, accountability, and customer trust in electronic banking systems.